QUALITY CONTROL ANALYSIS TO REDUCE THE NUMBER OF DEFECTS IN THE PACKAGING OF PG KREMBOONG SUGAR PRODUCTS USING SEVEN TOOLS METHOD - Erdhianto, Yoniv (Tibuana, 2021)
Quality control is an activity that must be carried out by a company so that the products produced are in accordance with the standards set by the company in order to meet customer satisfaction. This research was conducted in order to obtain the results of the quality control analysis which then the results of the analysis will be used as an effort to reduce the number of defects in product packaging in the future at PG Kremboong. This research in solving the problem using the seven tools method. This seven tools method uses 7 quality control tools, namely Check Sheet, Control Chart, Cause and Effect Diagram, Pareto Diagram, Histogram, Scatter Diagram and Stratification so that a quantitative measurement is produced that shows the extent to which management objectives have been achieved. From the analysis using the seven tools, the defects in granulated sugar with 50 kg packages were produced, namely, less light prints (146), torn packages (299), dirty packages (224) and loose seams (200). The defect with torn packaging is the most dominant type of defect. Improvement steps to reduce the number of defects in sugar packaging in the future are carried out on 5 factors, namely humans, methods, machines, materials and the environment based on a comparison between the causes of the problem and the standards applicable in the company.